2019
DOI: 10.26623/themessenger.v11i2.1317
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation Behavior and Risk of Stunting: Understanding the Discourse of a Public Service Announcement

Abstract: District Health Office of North Lombok Regency is developed a Public Service Announcement (PSA) to dealing with high stunting prevalence, by inform people about poor sanitation behavior and stunting. Using SaniFOAM framework, this study aimed to critically analyzed the sanitation behavior, its setting, narratives, images, conversations conveyed by the PSA and their intertextuality with socio-cultural background of the rural society, to see if it's an effective communication media in advocating public to stop o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
(23 reference statements)
0
14
0
3
Order By: Relevance
“…Another study conducted in rural Zimbabwe employing cluster-randomized trials found that WASH (Water, Sanitation, and Hygiene) practices implemented in rural areas are unlikely to reduce stunting [ 16 ]. However, few studies found that sanitation and defecation significantly affect stunting among children [ 24 ]. A study conducted in Indian settings utilizing NFHS data concluded that the practice of open defecation influences the inequality in stunting [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in rural Zimbabwe employing cluster-randomized trials found that WASH (Water, Sanitation, and Hygiene) practices implemented in rural areas are unlikely to reduce stunting [ 16 ]. However, few studies found that sanitation and defecation significantly affect stunting among children [ 24 ]. A study conducted in Indian settings utilizing NFHS data concluded that the practice of open defecation influences the inequality in stunting [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existing reality is not the real reality, but the result of all kinds of constructions carried out by the parties involved in it. The critical paradigm tries to define social science as a process that critically seeks to reveal the real structures of illusions, false needs that are visible from the material world intending to form a social awareness to improve and change the conditions of human life (Liem et al, 2019). Nyimak Journal of Communication, Vol.…”
Section: Methodsmentioning
confidence: 99%
“…The firstperson effect had a bigger impact on promotional activities than it did on contribution behaviours and largely mediated the influence of message desirability on promotional behaviours. Liem, Marta, & Panggabean (2019) critically analysed the sanitation behaviour of Indonesians through conversations regarding the effectiveness of a PSA meant to deal with the prevalence of stunting in Indonesia by informing people about poor sanitation behaviour and stunting. Rooted in the fact that PSAs can influence behavioural change, a study proposed a way to improve the automatic smoking detection system by automatically displaying a PSA about the hazard of smoking in public when the sensors triggered an alarm after detecting a certain level of smoke (Arief et al, 2020).…”
Section: Public Service Announcementmentioning
confidence: 99%